Copper foams in water treatment technology: Removal of hexavalent chromium. (15th December 2015) - Stergioudi, F.; Kaprara, E.; Simeonidis, K.; Sagris, D.; Mitrakas, M.; Vourlias, G.; Michailidis, N.
Abstract: Open-cell copper foams were prepared using a space holder technique and tested as filter-beds for the uptake and reduction of Cr(VI) in drinking water. The use of raw cane sugar as a space holder provides an environmentally friendly method for the production of foams with controllable porous network characteristics. Specifically, by applying a sugar volume of 70–80% with particle sizes in the range of 0.35–0.70 mm, it was possible to obtain final porosity of 65%, high structural stability, and enhanced interconnectivity of macropores required for the free flow of treated water. Smaller sugar particles ensure a smaller pore size and a higher specific surface area, favoring the interaction of water with the effective copper surface. Column tests indicated that a realistic filtering system using the Cu-foam can operate with complete Cr(VI) removal and minimum Cu leaching in the pH 7 ± 0.2 range, capturing chromium in the form of Cr(III) and Cr(VI) oxides. Chromium is homogeneously distributed and incorporated into the copper porous network allowing an almost unlimited lifetime of effective use compared to common adsorbents. Graphical abstract: Highlights: Open-cell copper foams were prepared using a space holder technique. Raw cane sugar used as a space holder is effective and environmentally friendly. Cu-foams were tested as filter-beds for the uptake and reduction of Cr(VI) in water. Column tests proved absolute Cr(VI) removal with minimum Cu leaching. An almost unlimited lifetime of effective use can be obtained.